The factors influencing employee job perfomance among educators in higher educational sector of Malaysia - Renusree, Manoharan (2024)
Malaysia’s socioeconomic growth is greatly influenced by the higher education sectors of Malaysia. The people who are maintaining and ensuring the quality and standard of the education sector is each educator in the higher education sectors of Malaysia. Despite maintaining the quality of education sector, they are also facing a lot of challenges such as changing in curriculum standards, technological improvements and identifying societal expectations. The main aim of this study is to examine the influence of work-life balance, employee engagement and job satisfaction on employee job performance among educators in higher education sectors of Malaysia. The proposing theoretical framework is underpinned by Social Exchange Theory (SET), discussed on the three independent variables in the study which is work-life balance, employee engagement and job satisfaction. The study adopts quantitative research method of primary source was utilized to collect the data from one hundred and fifty educator’s respondents by using random sampling technique and collected data has been analysed using Statistical Package for Social Science (SPSS). The data were analysed using different statistical techniques such as normality analysis, reliability analysis, descriptive of variable analysis, Pearson correlation analysis (Pearson Correlation Analysis) and regression analysis (Multiple Regression Analysis). The results demonstrated that the work-life balance, employee engagement and job satisfaction are positively related employee job performance. The findings from this study suggest that organization or the Human Resource department of the organization to identify the key factors which might affect the employee job performance and determine the best course of action to be taken to enhance the employee job performance